Partners in crime? Scandalous complicity between Rachilde and Jean Lorrain - Craske, HR (University of Nebraska Press, 2020)
Rachilde (1860–1953) and Jean Lorrain (1855–1906) co-opted the titillating appeal of taboos surrounding gender and sexuality for the means of self-promotion. Their approach constitutes a particularly productive yet ambivalent form of fin-desiècle literary complicity, integral to avant-garde sociability. This article analyzes their media-savvy contributions to a polemical debate surrounding the bas bleu figure, in a review called Le Zig-Zag. In these exchanges, their adoption of sexually ambiguous media personae was fundamentally ambivalent, acting simultaneously as collaborative performance and self-defense mechanism. By orchestrating the revelation of risqué biographical anecdotes, the pair wagered their reputations and friendships in exchange for infamy. They were enabled and abetted in their construction of subversive solidarity by structures and techniques specific to periodical culture. As exemplary “partners in crime,” Rachilde and Lorrain manipulated the appeal of the illicit alongside avant-garde forms of mediatized sociability, demonstrating the potential gain and risk involved in the process.